2001
DOI: 10.2737/pnw-gtr-510
|View full text |Cite
|
Sign up to set email alerts
|

Log and lumber grades as indicators of wood quality in 20- to 100-year-old Douglas-fir trees from thinned and unthinned stands.

Abstract: This report examines the differences in wood characteristics found in coastal Pacific Northwest Douglas-fir (Pseudotsuga mensziesii (Mirb.) Franco) trees harvested at the age of 70 to 100 years old to wood characteristics of trees harvested at the age of 40 to 60 years. Comparisons of differences in domestic log grades suggest that the proportion of log volume in the higher grades (Special Mill and No. 2 Sawmill) increased with both stand age and tree size. Simulation of lumber grade yields based on log charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Projection of lumber recovery by using sawing simulation models is becoming an accepted alternative to more expensive empirical wood product recovery studies (Todoroki, 1990(Todoroki, , 1995Steele et al, 1994;Pont et al, 1999). Inexpensive techniques have been developed to diagram the branch size and position in logs either for sawing simulations to estimate lumber grade yield (Barbour et al, 1999) or to combine this information with other log characteristics, e.g., growth rate and diameter, to estimate log grade yields (Barbour and Parry, 2001). These techniques would be appropriate for use in southeast Alaska and could be incorporated into evaluations of other thinning trials or remeasurements of existing spacing trials.…”
Section: Lumber Characteristicsmentioning
confidence: 99%
“…Projection of lumber recovery by using sawing simulation models is becoming an accepted alternative to more expensive empirical wood product recovery studies (Todoroki, 1990(Todoroki, , 1995Steele et al, 1994;Pont et al, 1999). Inexpensive techniques have been developed to diagram the branch size and position in logs either for sawing simulations to estimate lumber grade yield (Barbour et al, 1999) or to combine this information with other log characteristics, e.g., growth rate and diameter, to estimate log grade yields (Barbour and Parry, 2001). These techniques would be appropriate for use in southeast Alaska and could be incorporated into evaluations of other thinning trials or remeasurements of existing spacing trials.…”
Section: Lumber Characteristicsmentioning
confidence: 99%
“…Examination of log grades and sorts, product recovery studies, and discussions with log buyers indicate that the four following log characteristics predominate in log specifications: minimum rings per inch, minimum log diameter, maximum knot diameter, and maximum length [9][10][11]. Unfortunately, current log grades are not always indicative of lumber quality recovered during processing [2,12].…”
Section: Important Log Characteristics and How They Can Be Assessed Imentioning
confidence: 99%
“…Product recovery researchers have found that a measurable log attribute referred to as largest limb average diameter (LLAD) [2], also known as branch index or BIX [9], is a good predictor of product grade recovery. LLAD is obtained by measuring the diameter of the largest knot in each lengthwise quadrant or face of the log and calculating the average (Figure 4).…”
Section: Important Log Characteristics and How They Can Be Assessed Imentioning
confidence: 99%
“…Ty p i c a l l y, each log grade or log sort has a maximum knot diameter (Bowers 1997) and product recovery researchers have found that largest limb average diameter (LLAD, Fahey et al 1991) also known as branch index (bix, Barbour & Parry 2001), defined as the average of the largest diameter knot in each of the four quadrants or faces of the log surface, is a good predictor of product grade recovery from a log. One can hypothesize that the diameter of the largest knot or LLAD, measured with a caliper on the lower bole, would be highly correlated with the largest knot diameter or LLAD of logs within the tree.…”
Section: Knot Diametermentioning
confidence: 99%